Pembuatan Media Pembelajaran Berbasis Smartphone Memanfaatkan Aplikasi Quizlet, Quizizz, dan Perangkat Lunak EclipseCrossword - Eric Kunto Aribowo; Ari Purwanto (Universitas Mathla'ul Anwar Banten, 2021)
CREATING LEARNING MEDIA BASED ON SMARTPHONE USING QUIZLET, QUIZIZZ, AND ECLIPSECROSSWORD SOFTWARE. Most secondary school teachers still maintain conventional learning models, such as STAD, Role Playing, Two Stay Two Stray, Numbered Head Together that have minimal adoption of technology into the classrooms. Consequently, collaboration as one of the must-haves 21st century learners’ skills hard to be fulfilled. This paper presents best practices about mobile learning training which continues with its practice in the classroom. In-house training and assignment, Quizlet, Quizizz and EclipseCrossword used to create flash cards, digital quizzes and crossword. The training results show the high level of enthusiasm and motivation of participants in creating and preparing mobile-based learning. The results of the assignments and the performance of the training practiced in the classes prove the increasing engagement of students in learning and trying new experiences.